(untitled) (Global Journal of Computer Science and Technology, 2013)
In this paper, we present a system to control home appliances from a computer. The system is designed for controlling the ON/OFF mode of different home appliances such as light, fan, TV, air-condition and so on. The appliances are connected to a computer through a programmed PIC16F73 microcontroller. An USB interface is used to connect the microcontroller with a computer. The program for the PIC16F73 has been written in micro C language. All the commands are carried out from a software layout running on a computer to control the home appliances.